2019
DOI: 10.1021/acsnano.8b08911
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Self-Healing Liquid Films for Ultradurable Electronics

Abstract: Resistive strain sensors play a crucial role in the development of flexible and stretchable electronics because of their excellent sensitivity and conformability. However, such sensors suffer from poor durability because of the low adhesion strength between the solid conductive layer and polymer and the irreparable dry friction inside the conventional solid conductive layers. Here, inspired from the structures and excellent abrasion resistance of tear films on animal corneas, we demonstrate ultradurable strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…To endow LIG electrodes with better adhesivity, the mixture of the silicone base and crosslinker of the PDMS‐based elastomer along with a trace of ethoxylated polyethylenimine (PEIE) is painted on the area outside of LIG, which has been previously reported to improve the stretchability, softness, and adhesion of PDMS. [ 25–28 ] The compliant surface and dangling bounds enhance the adhesion of PDMS/PEIE. [ 25 ] Eventually, the sample is cured at 90 °C for 1 h, forming single‐sided adhesive epidermal electrodes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To endow LIG electrodes with better adhesivity, the mixture of the silicone base and crosslinker of the PDMS‐based elastomer along with a trace of ethoxylated polyethylenimine (PEIE) is painted on the area outside of LIG, which has been previously reported to improve the stretchability, softness, and adhesion of PDMS. [ 25–28 ] The compliant surface and dangling bounds enhance the adhesion of PDMS/PEIE. [ 25 ] Eventually, the sample is cured at 90 °C for 1 h, forming single‐sided adhesive epidermal electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…Till now, PEIE‐modified PDMS has been used to prepare adhensive flexible electronics. [ 9,26–28 ] Although no skin irritation was reported, the toxicity and biocompatibility of PEIE‐modified PDMS are still under research and it has not been concluded. This issue should be confirmed by a larger number of subjects and a series of cell incubation before practical use.…”
Section: Resultsmentioning
confidence: 99%
“…As a numerous source of inspiration, creatures in nature have evolved over millions of years, creating and achieving many special futures and properties, which provide unique structure and material sources for researchers to imitate . Thus, recently, the bioinspired self‐healing surface materials have become a hotspot owing to its widely recognized advantages . Up to date, some works have made obvious progresses by miming vascular systems and plant leaf surfaces .…”
Section: Discussionmentioning
confidence: 99%
“…The self-healing mechanism behind these materials have been largely categorized as extrinsic or intrinsic self-healing with extrinsic self-healing mechanism relying on dispersed healing agents to help repair damage. For electrical self-healing, examples of extrinsic self-healing sensors are those that involve liquid metals and ionic liquid-based active components which reflow to allow intermixing of materials at the reconnected interface [ 194 , 195 ]. This extrinsic mechanism is reliable but limited in the number of times it can be healed whereas intrinsic self-healing is dependent upon dynamic reversible covalent or non-covalent bonds which can allow the system to heal repeatedly through reorganization of the polymer matrix and often pertains to mechanical self-healing.…”
Section: Mechanical Sensor Characteristics Of Interestmentioning
confidence: 99%